Comparing Online vs. Face-to-Face Graduate Student Outcomes and Performance in CSD : A Comparative Review - Hemmerich, Abby; Steines, Emma; Symons, Emily (My University, 2018)
In today’s technology driven world, many college students have the option to take courses via online modalities. More than 25% of students in higher education are enrolled as online students (Allen & Seaman, 2010). Online courses can potentially provide the same standard of education as a face-to-face education (Bowen, Chingos, Lack, & Nygren, 2013). Previous research into student performance in online versus face-to-face courses has suggested that face-to-face students perform better (Edmonds, 2006; Young & Duncan, 2014).The purpose of the current study is to compare student performance in the online vs. face-to-face modality.
Color poster with text, images, and graphs.
Keywords: College students; Online education; Communication sciences and disorders; Distance education; Posters